The Impact of the Coronavirus Pandemic on Supply Chain: A Case of Egyptian Market - EL Sakty, Khaled (The Arab Journal of Administration, 2022)
COVID-19 is considered as a supply shock and a demand shock. It is claimed that current global supply chain practices have limited capabilities and do not allow for systemic exploration of alternate risk strategies. Therefore, the main purpose of this paper is to evaluate the impact of COVID-19 on supply chain performance, and to investigate the most suitable global supply chain risk strategies have been taken by Egyptian companies within a global supply chain setting. The research approach is based on a global survey of supply chain risk by 92 impacted companies in nine industries. It is evident as a finding that coronavirus pandemic (COVID-19) is causing major supply chain disruptions. Consequently, global risks are raised as strong and immediate impact on the supply chain performance since some key players are temporarily unavailable such as manufacturers, distributers, and suppliers. This leads to materials, semi-finished and finished goods shortage, longer lead times than originally anticipated, reduced revenue and service levels, where planned customers’ demands can no longer be met. The originality of this paper that it provides an empirical exploration of the global supply chain risk strategies experienced in the context of COVID-19. As a practical implication, the results of the survey questions conducted in this paper display practically the right global supply chain risk strategies to improve decision-making. This includes securing the sourcing with nearshore and local sourcing, the adoption of multiple sources, maintain buffer inventory, and reducing the number of small DC. This helps to reduce the impact of such global risk events.